The need for and use of panel data - Hans-Jürgen Andreß (IZA World of Labor, 2017)
Stability and change are essential elements of social reality and economic progress. Cross-sectional surveys are a means of providing information on specific issues at a particular point in time, though without providing any information about the prevailing stability. Limited information on change can be obtained by retrospective questioning, but this is often impaired by “recall bias.” However, valid information on change is essential for assessing whether phenomena such as poverty are permanent or only temporary. Panel data analyses can address these problems as well as provide an essential tool for effective policy design.
Keywords: C81; C83; J01; J10; 330; panel data; panel attrition; individual change; cohort analysis; omitted variable bias; selection